Narrating Our History: Selections from a Dialogue among Queer Media Artists from the African Diaspora - Ferrera-Balanquet, Raúl; Harris, Thomas Allen; Frilot, Shari; Gilliam, Leah; Suggs, Dawn; Taylor, Jocelyn; Welbon, Yvonne; Juhasz, Alexandra (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The first time I spoke in public about my work was during the Los Angeles Lesbian and Gay Festival in 1990. Cheryl Dunye was the only other woman of color on the panel. When I asked a question regarding funding, I naïvely stated that funding was not a prob lem for me considering the fact that my work at that time was of medium to low production quality. I had minimal access to a low-end production facility, and my piece was only five minutes long. I was alluding to the fact that it has been “easy” for me.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Documentary Practice and Transnational Feminist Theory - White, Patricia (A Companion to Contemporary Documentary Film, 2015)
This paper looks at five documentaries on activism around ending the practice of female genital cutting (FGC) in Africa. All were made by or in partnership with UK and US producers and are distributed by the New York-based non-profit media arts organization Women Make Movies. By tracing changing political and representational strategies in feminist documentaries on the issue and the varying terms on which the films engage their subjects and address their viewers, the chapter aims to put the specificity of independent documentary formats, practices, and institutions in dialogue with feminist theoretical critiques of the wider discourse on women's human rights. The chapter looks at Kaplan and Grewal's critique of the neo-colonialism of Alice Walker and Pratibha Parmar's Warrior Marks, the observational strategies of Kim Longinotto's The Day I Will Never Forget, the diasporic dimensions of Mrs. Goundo's Daughter and Sarabah, and the visual rhetoric of human rights models in Equality Now's Africa Rising. The cultural field of documentary constitutes a public sphere in which activist and theoretical debate, contested reception, and continually renewed cultural production articulate the productively shifting terms of transnational feminism.
Section: 10 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781118884584.ch10
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé